Flying aptitude tests for surgeons - Park, Hyunmi (2017)
Aims: To test whether the Flying Aptitude Test, the Royal Air Force’s selection aptitude test, can be used for surgical skills testing by correlating it to both open and minimally invasive surgical simulated tests. The introduction of such test at the onset of post graduate training could offer guidance and encouragement on a career in surgery.